Bawal centre / Nur Afiqah Ramizah Ramli, Noor Faiqa Elishya Mohd Saringat and Syahreena Waheeda Mohammad Noor - Ramli, Nur Afiqah Ramizah; Mohd Saringat, Noor Faiqa Elishya; Mohammad Noor, Syahreena Waheeda (2017)
Our business and administration will base on Business Registration Act (1956) and our type of business is partnership.